Risk-factor profiles for chronic diseases of lifestyle and metabolic syndrome in an urban and rural setting in South Africa - Sanet van Zyl; Lynette J. van der Merwe; Corinna M. Walsh; Andries J. Groenewald; Francois C. van Rooyen (AOSIS, 2012)
Background: Chronic lifestyle diseases share similar modifiable risk factors, including hypertension, tobacco smoking, diabetes, obesity, hyperlipidaemia and physical inactivity. Metabolic syndrome refers to the cluster of risk factors that increases the risk for developing type 2 diabetes mellitus (DM) and cardiovascular disease.Objectives: The study aimed to assess health status and identify distinct risk-factor profiles for both chronic lifestyle diseases and metabolic syndrome in rural and urban communities in central South Africa.Methods: The investigation formed part of the Assuring Health for All in the Free State (AHA-FS) study. During interviews by trained researchers, household socio-demographic and health information, diet, risk factors (i.e. history of hypertension and/or diabetes) and habits (e.g. smoking and inadequate physical activity levels) were determined. Adult participants underwent anthropometric evaluation, medical examination and blood sampling. Results: The risk-factor profile for chronic lifestyle diseases revealed that self-reported hypertension and physical inactivity were ranked the highest risk factor for the rural and urban groups respectively. The cumulative risk-factor profile showed that 40.1% of the rural and 34.4% of the urban study population had three or more risk factors for chronic lifestyle diseases. Furthermore, 52.2% of rural and 39.7% of urban participants had three or more risk factors for metabolic syndrome.Conclusion: This study confirmed that the worldwide increase in the prevalence of chronic lifestyle diseases can be attributed to a more sedentary lifestyle, illustrated in the urban study population, and increasing obesity. The rural study population had a higher prevalence of risk factors for metabolic syndrome.